Patterns of inpatient antibiotic use and antimicrobial resistance in the surgical wards of a Ugandan tertiary hospital: A mixed methods study - Fiona Mutesi Magololo; Dathan Byonanebye; Flavia Dhikusooka; Adelline Twimukye; Doreen Agaba; Ellon Twinomuhwezi; Hope Mackline; Edith Namakula; Alex Emmanuel Elobu; Norbert Orwotho Tholith; Francis Kakooza; Andrew Kambugu; et al. (PLoS ONE, 2026)
Background Inappropriate antibiotic use in surgical wards is a major driver of antimicrobial resistance (AMR), especially in low- and middle-income countries, where empirical prescribing is common. This study assessed inpatient antibiotic use and AMR patterns, integrating these findings with qualitative in-depth interviews (IDIs) which explored determinants of prescribing practices. Methods A convergent mixed methods study design was employed on the surgical wards of Mulago National Referral Hospital (MNRH) in Uganda. Quantitative data was collected through Point Prevalence Surveys (PPS) of antibiotic use and retrospective analysis of routine laboratory AMR data. Qualitative data was obtained through IDIs with healthcare workers (HCWs). Quantitative data was analysed using R version 4.2.2 and STATA 19. In-depth interviews were recorded and transcribed verbatim, open coded and then analysed using NVivo 12. Results Of 303 total surgical inpatients, 193/303 (63.7%) (95% CI: 58.0–69.12) were receiving at least one of the 281 antibiotic prescriptions and were included in this study. Surgical antibiotic prophylaxis (SAP) accounted for 256/281 (91.1%) of all antibiotic prescriptions, with 239/256 (93.4%) SAP extending beyond the first 24 hours. Ceftriaxone 89/281 (31.7%) (95% CI: 26.27–37.46), metronidazole 66/281 (23.5%) (95% CI: 18.66–28.89) and levofloxacin 24/281 (8.5%) (95% CI: 11.61–20.44) were most prescribed antibiotic agents. Watch category antibiotics were most used 152/281 (54.1%) (95%: 48.08–60.08), followed by Access category 129/281 (45.9%) (95% CI: 39.9–51.9). Although HCWs demonstrated awareness of AMS principles, formal stewardship systems were fragmented, and prescribing behaviour was strongly influenced by laboratory constraints, infection prevention and control (IPC) gaps and systemic challenges. Conclusion Prolonged SAP and Watch category predominant prescribing occur within a context of high AMR prevalence and constrained AMS infrastructure. Integrated AMS interventions combining institutional antibiograms and their reinforcement, audit and feedback mechanisms, establishment of clear AMS structures and laboratory capacity strengthening are urgently needed to mitigate AMR and optimize surgical antibiotic use.